Botanical Journal of the Linnean Society - Botanical Journal of the Linnean Society (Oxford University Press, 2026)
The Botanical Journal of the Linnean Society publishes original papers relating to the biology of both plants and fungi. The journal was first published in 1856 and evolved from the societies journal Transactions, which published early papers by Darwin and Wallace.
FI 0.65
Q2
Keywords: Life Sciences; Plant Science; Ciencias de la vida; Botánica; Acuerdos transformativos; Transformative agreements; Cambio climático; Biología comparada; Ecología; Biología evolutiva; Micología; Inferencia filogenética; Ciencias vegetales; Sistemática